Electrical design guide for commercial buildings / William H. Clark - Clark, William H.
Shows you step by step how to organize, layout and circuit, and complete the design of electrical power and telephone/communications systems for commercial and industrial buildings. This handy guide gives you all the information and tables you need within a comprehensive step-by-step map of the entire design process. You also get a rich assortment of schematics, sample details, typical floor plans, and model documents, the 10 most-used NEC tables, pro-level tips on energy conservation and cost cutting